The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/jbmr.1682
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of annexin A5, annexin A6, and collagen X causes no gross changes in matrix vesicle–mediated mineralization, but lack of collagen X affects hematopoiesis and the Th1/Th2 response

Abstract: Numerous biochemical studies have pointed to an essential role of annexin A5 (AnxA5), annexin A6 (AnxA6), and collagen X in matrix vesicle-mediated biomineralization during endochondral ossification and in osteoarthritis. By binding to the extracellular matrix protein collagen X and matrix vesicles, annexins were proposed to anchor matrix vesicles in the extracellular space of hypertrophic chondrocytes to initiate the calcification of cartilage. However, mineralization appears to be normal in mice lacking AnxA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 47 publications
3
33
0
3
Order By: Relevance
“…Nevertheless, a recent study found that Annexin A5 and Annexin A6-deficient mice developed no abnormal mineralization (34). The same group also found that the depletion of Annexin A5 and Annexin A6 in mice caused no gross changes in MV-mediated mineralization (35). The current results revealed no significant differences in Annexin A1, 2, 4, 5, 6, 7, or 11 expression for MVs from non-stimulated and stimulated cells.…”
Section: +supporting
confidence: 49%
“…Nevertheless, a recent study found that Annexin A5 and Annexin A6-deficient mice developed no abnormal mineralization (34). The same group also found that the depletion of Annexin A5 and Annexin A6 in mice caused no gross changes in MV-mediated mineralization (35). The current results revealed no significant differences in Annexin A1, 2, 4, 5, 6, 7, or 11 expression for MVs from non-stimulated and stimulated cells.…”
Section: +supporting
confidence: 49%
“…Yet, most important within the context of compensatory effects, upregulation of AnxA2, AnxA6 or AnxA7, all of which with overlapping expression, localization and activity pattern compared to AnxA5, was not observed in the AnxA5 KO mice. Nevertheless, the hypothesis of functional redundancy within the annexin family led to the generation of double KO mice lacking AnxA5 and AnxA6 (Belluoccio et al, 2010;Grskovic et al, 2012), which is described in more detail below (see the section 'AnxA6 KO mice' below; Tables 5 and 6). AnxA5 is believed to be involved in pregnancy loss and thrombosis associated with the antiphospholipid syndrome (Rand et al, 2010).…”
Section: Anxa5 Ko Micementioning
confidence: 99%
“…It was therefore concluded that AnxA5 and AnxA6 were not essential for mineralization in vivo. As both annexins were speculated to initiate the calcification of cartilage through collagen X-dependent pathways, Grskovic et al generated triple KO mice deficient of AnxA5, AnxA6 and collagen X (Grskovic et al, 2012). However, these mice did not show obvious abnormalities.…”
Section: Anxa6 Ko Micementioning
confidence: 99%
“…Kollagen X wechselwirkt möglicherweise auch mit Annexinen, um Matrixvesikel in der hypertrophen Epiphysenfuge zu platzieren und die Mineralisation zu steuern. In Kollagen-X-defizienten Mäusen ist die Mineralisation allerdings kaum beeinträchtigt ( [5]; . Abb.…”
Section: Enchondrale Ossifikationunclassified
“…Isolierte T-Zellen waren in vitro nicht zu einer Interleukin(IL)-2-abhängigen Th1-Antwort fähig. Eine starke Th1-Antwort ist aber für die Beseitigung intrazellulärer Infektionen erforderlich; das Ausbleiben einer angemessenen T-Zell-Reaktion in Kollagen-X-defizienten Mäusen könnte entsprechend die erhöhte Mortalität von Mutanten nach einer Infektion mit Toxoplasma gondii erklären [5]. Folglich ruft ein Verlust von Kollagen X, das ausschließlich in hypertrophen Chondrozyten und nicht etwa in Immunzellen exprimiert wird, subtile Defekte in der neonatalen Epiphysenfuge hervor, stört so die Lymphozytendifferenzierung im Knochenmark und beeinträchtigt die T-Zell-Funktion gegen Parasiten in adulten Tieren.…”
Section: Störungen Des Immunsystems In Kollagen-x-defizienten Oder -Tunclassified